FOREIGN TRADE AND ECONOMIC PERFORMANCE OF NIGERIA - Udokang, Nsisong Boniface (Scholar Express Journals, 2023)
Motivated by the need to undertake a comparative analysis of the economic effect of trade on multiple measures of economic performance in Nigeria, the study evaluates the influence of trade on economic performance in Nigeria over the period 1986 to 2021. The study employed the secondary data culled from the statistical bulletin of the Central Bank of Nigeria. The analytical techniques employed by the study includes; stationarity, Johansen's co-integration, error correction estimations and Granger causality tests. One-year lag length was determined as most appropriate for the foreign trade elements. The inflation rate model showed imports, exports and exchange rate as statistically valuable in determining Nigeria's economic performance. Further, imports were the only valuable determinant of Nigeria's employment rate which emphasizes the import dependency level of Nigeria which is crippling employment level. Finally, imports and exchange rate constitute valuable determinant of gross domestic product growth rate as an economic performance indicator in Nigeria. The Granger causality test results indicated that exports and exchange rate affects the level of inflation rate in Nigeria. On the other hand, Nigeria's employment rate is significantly supported by imports as well as balance of payment, while economic growth in Nigeria is promoted significantly by imports and exchange rate. In light of these findings, the study recommended that there should be policy consistency to attract foreign direct investment aimed at preventing capital flight by foreign investors
Keywords: Trade; Imports; Exports